Mastering resilience: Avicennia marina’s survival in hypersaline arid zones - Dhawi, Faten (Frontiers in Sustainable Food Systems, 2025)
Mangrove ecosystems, primarily Avicennia marina, are vital for sustainable development in hypersaline arid coastal regions such as the Persian Gulf, Red Sea, Horn of Africa, and Indian Ocean coast, providing nature-based solutions for carbon sequestration, soil stabilization, and coastal resilience. This review synthesizes strategies to enhance A. marina’s survival and productivity, aligning with UN SDGs 13 (Climate Action) and 15 (Life on Land). Evidence from 55+ studies shows blended seawater irrigation improves germination, balanced NPK fertilization boosts biomass by 35–60%, and elevation adjustments enhance hydrology, yielding 70–80% survival rates within 2–3 years. However, short-term studies limit insights into long-term sustainability, ecosystem stability, and adaptability. Soil amendments improve health but face scalability, cost, and ecological risks such as nutrient overload. A. marina tolerates 45 ppt salinity and benefits from tidal nutrients, yet waterlogging, nutrient imbalances, and heavy metal accumulation require precise management. Research gaps include field validation of amendments, heavy metal phytotoxicity data, and economic viability of carbon offset programs. Recommendations include tailored irrigation, optimized nutrient management, and hydrological engineering to maximize ecosystem services. Future research should focus on long-term trials, heavy metal assessments, cost–benefit analyses, and carbon offset economics to ensure resilient, sustainable mangrove restoration globally.